The reliability of the Greulich and Pyle atlas when applied to a Southern Turkish population - Gungor, Ozge Erken; Celikoglu, Mevlut; Kale, Burak; Gungor, Ahmet Yalcin; Sari, Zafer (European Journal of Dentistry, 2015)
Objective: The aim of this study was to evaluate the applicability of Greulich and Pyle (GP) method for Southern Turkish population. Materials and Methods: Hand and wrist radiographs of 535 patients (276 females, 259 males aged from 10 to 18 years) selected retrospectively from the archive. Skeletal age (SA) estimation was performed according to GP atlas. The chronological age (CA) and SA were compared using the Paired t-test. Results: The mean difference between the CA and SA ranged from 0.07 to 1.11 years. These differences between the CA and estimated SA were statistically significant in group I (10–10.90 years) (P < 0.001), group II (11–11.90 years) (P < 0.050), group III (12–12.90 years) (P < 0.001), group IV (13–13.90 years) (P < 0.010), and group V (14–14.90 years) (P < 0.001) for females. The mean difference between the CA and SA ranged from −0.41 to −1.79 years for females. These differences between the CA and estimated SA were statistically significant in all age groups. Conclusions: Statistically significant differences were found in the CA and SA assessed by GP method for the Southern Turkish sample. SA was significantly over-predicted in the 10–15 year ages in males and for 10–18 year ages for females. It is appropriate to use GP method in Southern Turkish children; however, a revision is needed for better results and to minimize the mistakes.
Keywords: Chronologic age; Greulich and Pyle atlas; skeletal age